Analysis of ship maneuvering difficulties under severe weather based on onboard measurements and realistic simulation of ocean environment. (1st February 2021) - Jing, Qianfeng; Sasa, Kenji; Chen, Chen; Yin, Yong; Yasukawa, Hironori; Terada, Daisuke
Abstract: The increasing demand for efficient, safe, and economic operation of ships has drawn attention to practical maneuvering behaviors for developing autonomous ships. Actual sailing conditions are reproduced to determine the relationship between environmental factors and ship steering records in rough seas. First, we generate realistic ocean environmental fields and analyze actual sea data. Then, we derive a modular maneuvering model reflecting environmental disturbances for further simulations. The correlation and multi regression analyses are performed based on measured data and environmental factors, which illustrate that the abnormal rudder angles are caused by reduced steering effectiveness. Finally, an attenuation function acting on the rudder normal forces is proposed to simulate this type of reduction. The time histories of maneuvering difficulties are selected as verification datasets. The maneuvers are simulated by adopting the attenuation function, and the simulation results show fair agreement with the measured data. The significant wave height, wind speed, mean wave period, current speed, wind apparent direction, and wave encounter angles are found to be the most statistically significant factors of rudder attenuation in the studied cases. The results and conclusions obtained from this study are of great significance for the further exploration of actual ship maneuvering behaviors in seas. Highlights: Problems to maintain course in actual sailing are investigated. Data from spatiotemporally varying environmental fields are collected. Measured data are utilized to reproduce realistic fields. Rudder attenuation under severe weather is found by a statistical analysis.